Undergraduates Perception of Accountability, Transparency and Participation in Civic Activities in Nigeran South Western States - Ogunbayo Oluwasegun (Eastasouth Institute, 2026)
This study examined undergraduates’ perception of accountability and transparency and participation in civic activities in Nigeran Southwestern States. Descriptive research design of the survey type was used in this study. The population of this study consisted of 872,100 undergraduate students, universities in Southwest, Nigeria. The sample for this study consisted of 1522 university undergraduates selected using multistage sampling procedure that include simple random, stratified and purposive sampling techniques. ‘Undergraduates Perception of Accountability and Transparency and Civic Activities Questionnaire’ (UPATCAQ) was used to collect data. Face and content validity of the instrument, were ensured by experts in the fields of Social Studies Education, and Tests and Measurement in the Faculty of education, Ekiti State University, Ado-Ekiti. Reliability of the instrument was ensured through test-retest method and a reliability coefficient of 0.88 was obtained. Data were analysed with descriptive and inferential statistics such as frequency counts, means, standard deviations, and percentages; and PPMC. It was reported that undergraduate have positive perception of accountability and transparency but their level of participation in civic activities was low. A significant relationship between perception of accountability and transparency and participation in civic activities. It was inferred that there was a general appreciation for the principle accountability and accountability among undergraduate students in Southwest, Nigeria Universities. It was recommended among others that Universities and relevant government agencies should institutionalize transparent governance practices within higher education systems.